The Breeding of Climbing Perch (Anabas Testudineus) With Meristic Phylogenetic Hybridization Technique Sampled From Three Types of Swamp Ecosystems - Slamat Slamat; Pahmi Ansyari; Ahmadi Ahmadi; Ririen Kartika (TROPICAL WETLAND JOURNAL, 2019)
This study provides a valuable information on the patterns of hybridization in producing Climbingperch’s fry which having a superior character to beneficially supports fish farming. The research wascarried out at Pokdakan Rawa Sejahtera Amuntai, South Kalimantan Province, Indonesia from June toDecember 2018. The hybridization procedures were applied to the selected broodstocks (total 135),which taken from three different types of habitats namely rain reservoirs, monotonous and tidalswamps. A complete random design was used as a research method with three treatments and ninerepetitions. A comprehensive investigation was done to provide the best performance among thetreatments. The results showed that the hybridized fish from monotonous swamp x tidal swamp wasthe most superior across the trials in term of fecundity (18,500 eggs), GSI (18.1%), hatching rate(89.5%), relative length growth (1,375%), relative weight growth (1,850%) and the percentage of birthfemale (84 %) with the lowest mortality rate (29%). For aquaculture practices, the use of the fryunisexual female would increase the fish growth 270% faster than the fry male.